Modulación del proceso de neurogénesis adulta en ratones: interacción entre el sistema serotonérgico y las neurotrofinas - Foltran, Rocío Beatriz (2022)
Adult hippocampal neurogenesis is a process that occurs in mammals throughout life. Of the factors that modulate it, it has been reported that both increases and decreases in the neurotransmitter serotonin (5-HT) facilitate the neurogenic effect. Likewise, brain-derived neurotrophic factor (BDNF) is a neurotrophin involved in survival processes and neuronal plasticity. To study this triangulation, we used a model of 5-HT increase through chronic administration of 5-HT antidepressants and two models of hyposerotonergia, one pharmacological and one genetic. After fine-tuning the oral administration of the drugs, we studied the effect of the modulation of 5-HT levels on the BDNF pathway and observed that both in the antidepressant model and in transgenic hyposerotonergic animals the pro-neurogenic effect is accompanied by an activation of the BDNFm/TrkB pathway. On the other hand, in the pharmacological model of hyposerotonergia, the increase in neuronal survival involves the pro-BDNF/p75 component of this pathway. These different serotonergic system/BDNF pathway configurations do not translate into similar performances in a pattern separation behavior. Our results allow us to better understand the mechanisms underlying the neurogenesis process.